Diskursus Konsep Dan Prinsip Akad dalam Hukum Islam - Cipta, Hendra (ASY SYAR'IYYAH: JURNAL ILMU SYARI'AH DAN PERBANKAN ISLAM, 2016)
Contract has an important role in the agreement and the engagement of either Islamic law or in the positive law. The existence of the contract with the Islamic principles would sustain the contract to the benefit and avoid deception and fraud between the parties. Islamic principles are based on permissible, voluntary, welfare and justice needs to be embedded in the Islamic contracts. If these principles are at parties, then the contract will not be a contract that is imperfect.